First report of Rhodnius montenegrensis (Hemiptera, Reduviidae, Triatominae) in Amazonas, Brazil - Fernanda Portela Madeira; André Luiz Rodrigues Menezes; Adila Costa de Jesus; Madson Huilber da Silva Moraes; Jader de Oliveira; João Aristeu da Rosa; Luís Marcelo Aranha Camargo; Dionatas Ulises de Oliveira Meneguetti; Paulo Sérgio Berrnarde (Revista da Sociedade Brasileira de Medicina Tropical, 2020)
Abstract INTRODUCTION: Triatomines are hematophagous insects of epidemiological importance because they are vectors of Chagas disease. We present here the first report of Rhodnius montenegrensis in Amazonas, Brazil. METHODS: Triatomines were collected from Attalea butyracea palm trees in the municipality of Guajará. RESULTS: Two adult female R. montenegrensis specimens were identified. CONCLUSIONS: The present study confirms that the number of triatomine species within the Amazon has increased from 10 to 11, and the number of Brazilian states with R. montenegrensis has increased from two to three.